2010
DOI: 10.1007/s00421-010-1678-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a long standing error in single-bolus determination of the hepatic extraction ratio for indocyanine green

Abstract: For approximately 50 years, hepatic clearance of indocyanine green (ICG) has been used to assess liver function. Steady-state infusion of ICG with simultaneous measurement of arterial and hepatic venous ICG concentrations provides unambiguous measures of the extraction ratio for ICG and the hepatic blood flow rate, but also requires cannulation of a hepatic vein. Transient clearance following injection of a single bolus of ICG, which typically involves only measurement of arterial ICG concentration, is a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…It is now the most widely used quantitative liver function test in the clinical setting. 31 ICG is a tricarbocyanine dye that binds to albumin 32,33 , alpha-1lipoproteins 28 , and β-lipoproteins. 32 It distributes uniformly in the blood within 2-3 minutes after intravenous injection of 25 mg or 50 mg ICG (dissolved in 5 mL or 10 mL sterile water, respectively).…”
Section: Indocyanine Green (Icg) Clearance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now the most widely used quantitative liver function test in the clinical setting. 31 ICG is a tricarbocyanine dye that binds to albumin 32,33 , alpha-1lipoproteins 28 , and β-lipoproteins. 32 It distributes uniformly in the blood within 2-3 minutes after intravenous injection of 25 mg or 50 mg ICG (dissolved in 5 mL or 10 mL sterile water, respectively).…”
Section: Indocyanine Green (Icg) Clearance Testmentioning
confidence: 99%
“…36 Under normal conditions, ICG has a high hepatic extraction rate, and its uptake is rate-limited by blood flow. 15,33 Additionally, the clearance of ICG from the blood is similar to that of various endogenous and exogenous substances such as bilirubin, hormones, drugs, and toxins. The ICG clearance test therefore reflects several important functional parameters of the liver, including blood flow-dependent clearance and transporter capacity.…”
Section: Indocyanine Green (Icg) Clearance Testmentioning
confidence: 99%
“…13 Exclusive hepatic extraction and photometric properties of ICG have yielded less invasive ICG plasma disappearance rate and ICG 15-min retention rate (ICG-R15), which measure hepatic parenchymal function rather than liver blood flow and are potentially subject to error. 14,15 …”
Section: Liver Imaging—unmet Needsmentioning
confidence: 99%
“…Indocyanine green (ICG) is a metabolically inert dye. It does not get metabolized or degraded in blood, is solely and actively excreted by hepatocytes, and is not reabsorbed via the enterohepatic pathway; hence, it is an ideal marker for liver function assessment 70–74. ICG is injected at a dosage 0.5 mg/kg intravenously; serum retention of ICG >15% at 15 minutes is generally considered inadequate75 although it has been reported that the safety cutoff can be as high as 20% for a Child-Pugh A patient 76.…”
Section: Patient Selectionmentioning
confidence: 99%